Does salivary microbiome reflect the functional activity profile of oral microbiota? - Elizaveta S. Klimenko; Ilya A. Igumnov; Daria P. Markova; Natalia L. Belkova; Larisa V. Suturina (Russian Open Medical Journal)
Human oral cavity is a diverse habitat, consisting of many locations with its microbiotas. It was proven that bacteria detected in saliva could be the indicators of disease and be useful for diagnosis, monitoring, and overall assessment of the patient health. As pilot research of microbial communities associated with polycystic ovary syndrome (PCOS), biomaterials were collected from two patients (saliva, the contents of gingival pockets) for sequencing the amplicon libraries V4-V6 of variable regions of the 16S rRNA gene. Our study aimed at comparing the taxonomic and functional profiles of different locations in the oral cavity. Material and Methods — DNA samples were sequenced using Illumina MiSeq; the qiime2-2020.2 and PICRUSt2 v2.4.1 software packages were used to process the sequencing results of the amplicon libraries. Results — We demonstrated that the salivary microbiome had a greater taxonomic diversity, compared with the microbiome of the periodontal pockets. Regarding the ratios of different taxonomic group abundances, the species ratio in the saliva community significantly differed from the ratio in periodontal pockets. The microbiota of the oral cavity was classified as a producing community, since many different biosynthetic pathways were predicted. Similar functional features were identified for microbial communities in other locations. Conclusions — Different locations in the biotope of the oral cavity have varying species richness of their communities and specific taxonomic composition. However, the microbiotas of different microniches perform similar metabolic functions. This finding allows considering the analysis of saliva microbiota sufficiently representative tool for characterization of the entire oral microbiome.